PENGARUH SUBSTITUSI AMPAS TAHU DAN PENAMBAHAN PISANG AMBON PADA SNACK BARKEDELAI UNTUK OLAHRAGAWAN (ASPEK DAYA TERIMA, EKONOMI DAN KANDUNGAN GIZI) Effect of Bean Curd Substitution and Addition of Ambonese Banana on Soybean Snack bar Formula for Athletes (Acceptability, Economic Value, and Nutritional Aspects) - Brilliant Anjar Saputro; Annis Catur Adi (Media Gizi Indonesia, 2020)
Degradation of sport performance in Indonesian athletes was recorded in Sea Games 2017 and FIFA rank in 2015. Some of athletes’ main problem are lack of stamina and endurance. These problem are caused by insuffi cient carbohydrate and energy intake. In addition, selection of tofu curd waste and banana are purposed to provide adequate potasium intake. This study was aimed to reveal the eff ect of bean curd waste and the addition of Ambonese bananas to the acceptability, nutritional value and economic value of the formulated snack bars.The used design was true experiment with completely randomized design. This study employed untrained panelists including athletes with weight restrictions (gymnastics and sports combat with weight classes) as many as 30 people.The percentage of bean curd waste substitution was P1: 12%; P2: 16%; P3: 25%, and 10% added banana. Statistical test results Friedman confi rmed a signifi cant diff erence in the level of preference on the texture and taste aspects between control and other formula. The results of the acceptability, nutritional value and economic value ranking obtained the optimum value in formula two (P2).Nutritional value for 100 grams of snack bar P2 (cohydrate: 41.6 g; fi ber: 8.7 g; potassium: 514 mg) has been able to contribute at least 10% of the daily energy needs of athletes. Laboratory test results for fi ber and potassium can meet 16.7% and 10.9% of the daily needs of athletes. Hence, formulated snack bar can be claimed to be high in fi ber and potassium products. The most aff ordable price of the formulated product was 7,000 IDR per 125 g which is more economical than the commercial soybean-based snack bar. Therefore, the formulated snack bar can be recommended as a complementary meal of athlete with weight restrictions.